Specificity of human nature - vampirism - Tomczyk, Jacek; Dygudaj, Anna (Studia Ecologiae et Bioethicae, 2008)
Every myth, regardless of its nature, refers back to some event placed in illio tempore. By this fact it constitutes a pattern to all situations and activities in which the event may reappear, the myth can degrade into an epical legend, a ballad or a roman, but it can also survive in a limited form in superstitions, customs and longings without losing neither its structure nor its meaning. In the history of mankind, the perception contributed to the formation of culture - the total of artifacts, both material and immaterial (spiritual or symbolic), these achievements, characteristic for particular society, constitute a model of social behavior. While interpreting the external world people relied on supernatural explanations to some extent, which depended on the level of intellectual development. Initially many facts were explained with the interference of dark, demonic powers, adopting diverse forms in people’s imagination, thanks to such interpretation of reality the vampire was born to existence. The vampire has undergone a peculiar evolution, the features of its character often changed and the figure was many times reborn in varied forms. Settled in present times, the silhouette of the vampire remains realistic in some people’s minds and has no tendency to modify. Its presence in modern times is mainly perceptible through the creation and development of vampire - worshiping sects. The following thesis is aimed to present the evolution of beliefs and picture of the vampire, as well as ancient practices and ways of treating people suspected of vampirism, the text enables a close look into the structure and functioning of modern vampire-related cults, it also attempts to explain the phenomenon of vampirism and its continuously increasing popularity.